Transcranial Direct Current Stimulation Effects on Athletes’ Cognitive Performance: An Exploratory Proof of Concept Trial - Borducchi, Davimar M. M.; Gomes, July Silveira; Akiba, Henrique; Cordeiro, Quirino; Borducchi, José Henrique M.; Valentin, Lívia Stocco Sanches; Borducchi, Gabrielle M.; Dias, Álvaro Machado (Frontiers in Psychiatry, 2016)
Among the 2016 Olympic and Paralympic Games unforgettable moments, one could not overlook performances by Phelps and Bolt, which challenge old premises about the maximum extension of individual supremacism in ultracompetitive modalities and the doping scandals. Different media channels resonated these two trends, with an unseen rise on discussions about traits and practices that may set ultrahigh performance athletes apart from the more ordinary ones. Yet, some key issues remain undebated. This paper aims to add to this debate, with a proof of concept trial, which investigates whether tDCS may serve as an aid for professional athletes. Ten professional athletes of three different modalities of (judo, N=4 athletes, swimming, N=3 athletes and rhythmic gymnastics, N=3 athletes) received anodal stimulation (2mA) for 20 minutes on the left dorsolateral prefrontal cortex for ten consecutive weekdays. We observed a positive effect of tDCS in their cognitive performance, including a significant improvement in alternated, sustained and divided attention and in memory scores. We also observed a decrease in Beck Depression Inventory scores (4.50 points) in this non-clinical population. These preliminary results suggest that tDCS sessions may translate into competitive advantages for professional athletes and recommend the deepening of the discussion on its ethical use in sports, which is ultimately tied to the wider debate around the risks and opportunities that neuromodulation brings to the table.